23 Talking about the future with homeless people with ill health: the need for a different conversation. Issue 3 (1st September 2017) - Hudson, Briony F; Shulman, Caroline; Low, Joseph; Hewett, Nigel; Daley, Julian; Davis, Sarah; Brophy, Niamh; Howard, Diana; Vivat, Bella; Kennedy, Peter; Stone, Patrick
Abstract : Introduction: Homelessness is associated with death at a young age, frequently related to physical and mental health problems complicated by drug or alcohol dependence (Stringfellow et al., 2015). Homeless people experience high symptom burden at the end-of-life (Tobey et al., 2016), yet access to palliative care services is limited (Shulman et al., In press). Conversations around future wishes and preferences with homeless people rarely take place. Aim: To explore the barriers to conversations about the future with unwell homeless people and alternative approaches to these difficult conversations. Methods: Focus groups and interviews were used to explore views and experiences around palliative care with currently and formerly homeless people (n=38), healthcare professionals (n=32), hostel and outreach staff (n=39) and drug and alcohol workers (n=4), from three London boroughs. Verbatim transcripts were analysed using thematic analysis. Results: Three themes were identified relating to the challenges of discussing future care preferences: the recovery focused nature of services; uncertainty around when and how to have conversations; fear of negative impact on the homeless person and staff. Conclusions: There is little acknowledgement, discussion or planning around the health needs of unwell homeless people who are at risk of dying, reducing opportunities for person-centred care. An approach that considers current and continuing care needs that accommodates potential improvements and deterioration is needed. Identifying those whose health is a concern, rather than those thought to be imminently dying may help to ensure the wishes and choices of homeless people are respected, if their health deteriorates. References: . Shulman C, Hudson BF, Low J, Hewett N, Daley J, Kennedy P, Davis S, Brophy N, Howard D, Vivat B, Stone P, (In press). Homelessness at the end of life: A qualitative analysis of the barriers in providing palliative care for people who are homeless. Palliative Medicine. . Stringfellow EJ, Kim TW, Pollio DE, Kertesz SG. Primary care provider experience and social support among homeless-experienced persons with tri-morbidity. Addiction science & clinical practice2015;10:A64–A64. . Tobey M, Manasson J, Decarlo K, Ciraldo-maryniuk K, Gaeta JM, Wilson E. Homeless Individuals Approaching the End of Life: Symptoms and Attitudes. Journal of Pain and Symptom Management2016; In press.